Sometimes we fall - De Sève, Randall (Random House Studio, 2024)
Baby Bear wants to climb a tree and eat delicious plums with Mama Bear but is overcome with a progression of worrisome possibilities, until Mama Bear gently reassures Baby Bear about the importance of taking risks.